KOPAJA: Edukasi Pencegahan Obesitas dan Gizi Seimbang bagi Pekerja Dewasa di Kota Serang - Siregar, Mukhlidah Hanun; Maulinda, Amal; Nuzuliansyah, Hesty Dwina; Aziza, Sazkia Rahma; Mulyaningsih, Silvi; Nursofiati, Siti; Susilawati, Susilawati (Madani : Indonesian Journal of Civil Society, 2025)
Obesity is a growing public health concern in Indonesia. Adult workers form a vulnerable group due to their sedentary lifestyles and time constraints. This community service activity aimed to provide education on obesity prevention and balanced nutrition for adult workers in Serang City. The implementation method included the preparation of educational materials, online dissemination through videos and interactive discussions via WhatsApp, and offline dissemination by distributing posters and stickers. Knowledge evaluation was conducted using pre- and post-tests on 12 workers. The results demonstrated a significant increase in knowledge after education (average pre-test score of 40.00 to 91.67 on the post-test, p < 0.001). This activity concludes that structured health education is effective in improving workers' knowledge about obesity, which is expected to encourage behavioral changes towards a healthier lifestyle.